A apropria????o da proposta curricular do programa S??o Paulo faz escola pelos professores de l??ngua portuguesa - Silva, Val??ria Andrade (2010)
The appropriation of the Curricular Proposal of S??o Paulo faz escola program into the Portuguese teachers school practice is focus of the analysis in this research, aiming to apprehend those teachers comprehension about the principles and fundaments guiding the Curricular Proposal and also to identify the changes in their teaching practice due to the implement of the program mentioned. The field research took place at state school unit in S??o Paulo state capital that serves only the ciclo II of Ensino Fundamental. Semi-structured interview were held with five Portuguese teachers and with the pedagogical coordinator along with non-structured observations of HTPCs and informal moments at the teachers room. At first we approach the different steps of the curriculum development as proposed by Sacrist??n (2000) and adopted in the theoretical and methodological course of this work because it considers the political, social, economical, cultural and administrative dimensions in the prescribed curriculum elaboration and it includes its presentation to the school agents, its re-signification and modeling by them until it is presented as active curriculum in teaching practices, always mediated by school conditioners. After that, we discuss the Curricular Proposal of S??o Paulo faz escola based on its documents, its implementation mechanisms and theoretical principles and fundaments expressed in it. The Portuguese Curricular Proposal elaborated by the SEE-SP and Teaching Plans made by the investigated school s teachers are presented with the purpose of identifying convergences and divergences from the prescribed curriculum. From the characterization of that school unit as the context of the teaching practice, in the third part of this paper, we analyzed this reform control mechanisms and the Portuguese teachers comprehension about the theoretical fundament of the Curricular Proposal based on the teachers and pedagogical coordinator reports, under the categories of appropriation and objectification and continuities e changes.